Caries Patterns in Primary Dentition in 3- to 5-Year-old Children. Medellín, Colombia (2019)
ABSTRACT: Introduction: early childhood caries (ECC) is a public health problem. Recognizing caries patterns in affected children can help improve oral health programs focused on the preschool population. The aim of this study was to identify caries patterns in 3- to 5-year-old children in a low to middle-low socioeconomic area. Methods: a calibrated dentist recorded caries lesions using ICDAS criteria in 548 children attending four day-care centers in a low to middle-low socioeconomic area. ECC and S-ECC prevalence and the proportion of affected teeth/surfaces by lesion type for homologous teeth were calculated. Results: a total of 419 (76.5%) and 238 (43.4%) children had ECC and S-ECC, respectively. Average dmft was 3.7±3.7 and average affected surfaces were 5.8±7.7. Occlusal surfaces showed the highest caries experience, varying from 17.7% to 36.1%, showing statistical significance when compared to other molar surfaces. The upper smooth anterior surfaces were affected from 0.2% to 17.2%, while lower smooth anterior surfaces showed values between 0.0% and 6.8%. The percentage of dental caries experience in second molars varies from 37.1% to 42%, while in lower central and lateral incisors the values range from 1.8% to 4.6%. Conclusion: the specific caries pattern in preschool children with high prevalent ECC from a middle-low-income area indicate the need to design programs aimed at detecting early sings of dental caries in specific locations, as well as disease control strategies.